Yao-Shan of traditional Chinese medicine: an old story for metabolic health - Yang, Shuangling; Yang, Hongzhi; Zhang, Yaxing (Frontiers in Pharmacology, 2023)
Type 2 diabetes mellitus, nonalcoholic fatty liver disease (NAFLD), cardio-cerebrovascular diseases (CCVDs), hyperuricemia and gout, and metabolic-related sexual dysfunction are metabolic diseases that affect human health in modern society. Scientists have made great efforts to investigate metabolic diseases using cell models in vitro or animal models in the past. However, the findings from cells or animals are difficult to translate into clinical applications due to factors such as the in vitro and in vivo differences; the differences in anatomy, physiology, and genetics between humans and animals; and the differences in microbiome–host interaction. The Chinese have extensively used the medicated diet of traditional Chinese medicine (TCM) (also named as Yao-Shan of TCM, Chinese Yao-Shan et al.) to maintain or improve cardiometabolic health for more than 2,200 years. These ancient classic diets of TCM are essential summaries of long-term life and clinical practices. Over the past 5 years, our group has made every effort to collect and sort out the classic Yao-Shan of TCM from the ancient TCM literature since Spring and Autumn and Warring States Period, especially these are involved in the prevention and treatment of metabolic diseases, such as diabetes, NAFLD, CCVDs, hyperuricemia and gout, and sexual dysfunction. Here, we summarized and discussed the classic Yao-Shan of TCM for metabolic diseases according to the time recorded in the ancient literature, and revised the Latin names of the raw materials in these Yao-Shan of TCM. Moreover, the modern medicine evidences of some Yao-Shan of TCM on metabolic diseases have also been summarized and emphasized in here. However, the exact composition (in terms of ratios), preparation process, and dosage of many Yao-Shan are not standardized, and their main active ingredients are vague. Uncovering the mystery of Yao-Shan of TCM through modern biological and chemical strategies will help us open a door, which is ancient but now looks new, to modulate metabolic homeostasis and diseases.